Differences in Arteriovenous Fistula Maturation between Diabetes Mellitus and Non-Diabetes Mellitus in Chronic Renal Failure Patients in Padang - Richard Santosa; Raflis Rustam; Vendry Rivaldy (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2022)
Background: Arteriovenous fistula (AVF) is the preferred vascular access for hemodialysis (HD). Several factors can affect AVF maturity, such as diabetes. This study aims to determine the differences in the maturation of arteriovenous fistulas between diabetes mellitus and non-diabetes mellitus in patients with chronic kidney failure in Padang. Methods: This was a comparative cross-sectional study of patients with chronic kidney failure who underwent arteriovenous fistula surgery in Padang. The sampling technique in this study was consecutive sampling. The analysis was carried out using statistical analysis according to the existing data scale and using SPSS software. Results: This study involved 46 patients with chronic kidney failure who underwent arteriovenous fistula surgery in Padang, of which 23 patients with diabetes mellitus and 23 patients with non-diabetes mellitus. The diameter of the arteriovenous fistula between diabetes mellitus and non-diabetes mellitus in patients with chronic renal failure had a significant difference (p<0.05). There was no significant difference in flow, depth, and maturation of arteriovenous fistulas in patients with diabetes mellitus and non-diabetes mellitus with chronic renal failure. Conclusion: There is no difference in the maturation of arteriovenous fistula between patients with diabetes mellitus and non-diabetes mellitus